Block observations of neighbourhood physical disorder are associated with neighbourhood crime, firearm injuries and deaths, and teen births. Issue 10 (15th September 2005) - Wei, Evelyn; Hipwell, Alison; Pardini, Dustin; Beyers, Jennifer M; Loeber, Rolf
Abstract : Study objective: To provide reliability information for a brief observational measure of physical disorder and determine its relation with neighbourhood level crime and health variables after controlling for census based measures of concentrated poverty and minority concentration. Design: Psychometric analysis of block observation data comprising a brief measure of neighbourhood physical disorder, and cross sectional analysis of neighbourhood physical disorder, neighbourhood crime and birth statistics, and neighbourhood level poverty and minority concentration. Setting: Pittsburgh, Pennsylvania, US (2000 population = 334 563). Participants: Pittsburgh neighbourhoods (n = 82) and their residents (as reflected in neighbourhood level statistics). Main results: The physical disorder index showed adequate reliability and validity and was associated significantly with rates of crime, firearm injuries and homicides, and teen births, while controlling for concentrated poverty and minority population. Conclusions: This brief measure of neighbourhood physical disorder may help increase our understanding of how community level factors reflect health and crime outcomes.